Waria dalam Kajian Antropologi Tubuh - Agung Suharyanto (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2015)
Focus of this writing is around struggle of transvestites in itself, identity and social life. Transvestites looks at themselves, as more important in comparison with viewing their world as excluded and accused, or merely class and racial struggle. It minds that identity itself is not merely formed individually, but also socially, namely when behaviour of someone presented socially. Transvestites could be defined when a man behaves as woman, which generally considered that it is transvestites, although its world truly is not as simple as that. Otherwise, someone who have really been established transvestity, and then become prostitute, so it is not trans-vestites  which is considered as that identity, but prostitute. Therefore, between individual behaviour and reality in a community, dialectical process on relation between body and social is taking place.